2014
DOI: 10.1103/physrevlett.113.113601
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lived Quasistationary Coherences in aV-type System Driven by Incoherent Light

Abstract: We present a theoretical study of noise-induced quantum coherences in a model three-level V-type system interacting with incoherent radiation, an important prototype for a wide range of physical systems ranging from trapped ions to biomolecules and quantum dots. By solving the quantum optical equations of motion, we obtain analytic expressions for the noise-induced coherences and show that they exhibit an oscillating behavior in the limit of large excited level spacing Δ (Δ/γ≫1, where γ is the radiative decay … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
189
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(199 citation statements)
references
References 32 publications
7
189
1
Order By: Relevance
“…localization properties) determines the photoreaction efficiency or quantum yield 29 . In the opposite regime of non-orthogonal transition dipoles, we observe nontrivial dynamical effects due to the Agarwal-Fano interference 19 , prior to long time relaxation to energy eigenstates.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…localization properties) determines the photoreaction efficiency or quantum yield 29 . In the opposite regime of non-orthogonal transition dipoles, we observe nontrivial dynamical effects due to the Agarwal-Fano interference 19 , prior to long time relaxation to energy eigenstates.…”
Section: Introductionmentioning
confidence: 91%
“…[8][9][10][11], an entirely different kind of quantum coherence among the excited states is known to arise [12][13][14][15][16][17][18] , and persist for a long time 19 under incoherent light illumination. These coherences are due to the Agarwal-Fano (AF) interference between different incoherent light-induced transition pathways 12,18,20,21 , and have much in common with previously explored quantum optical phenomena such as vacuum-induced coherence, lasing without inversion, electromagnetically induced transparency, and quantum control 18,19,22 . This kind of noise-induced coherence has recently attracted much interest in view of its potential to enhance the efficiency of quantum heat engines, both natural and artificially designed 13,14,16 .…”
Section: Introductionmentioning
confidence: 99%
“…The system-bath coupling Hamiltonian (II.4,II.5)) is written in the original basis as 15) while in the normal mode basis ((…”
Section: The Model and The General Solution Of The Equations Of Mmentioning
confidence: 99%
“…Recent experimental studies [37][38][39] have demonstrated the feasibility of coupling various quantum systems to non-equilibrium baths, and of tailoring the environmental degrees of freedom. Recent theoretical analysis [15] of a V-type molecular system showed the possibility of long-lived coherences despite noise-induced decoherence, and ref. [16] reports the emergence of steady-state entanglement in the case of finite dimensional coupled systems such as superconducting qubits or quantum dots.…”
mentioning
confidence: 99%
See 1 more Smart Citation